Critical Analysis of the News Article “Public Losses Due to Adulterated Pertamax” Published by Tempo.Com Norman Fairclough’s Perspective - Isro'atul Choliliyah; Hanik Mahliatussikah (Deiksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to reveal the construction of discourse oncorruption at Pertamina in a Tempo.com news article entitled“Corruption at Pertamina: Public Losses Due to AdulteratedPertamax Estimated at Rp 17.4 Trillion per Year” (February 28,2025) by applying Norman Fairclough's Critical Discourse Analysis(CDA) model. The primary data consists of the full text of the newsarticle. The analysis was conducted across three dimensions: thetextual dimension, the discursive-practical dimension, and thesocial-practical dimension. The results indicate that the news textnot only presents facts but also reinforces the credibility of the newsby presenting qualitative data, promoting social control, andmobilizing public opinion. Thus, this discourse functions as anarena for ideological resistance and social change, affirming the roleof digital media in demanding transparency and institutionalaccountability.